The Influence of Perceived Usefulness, Trust, and Ease of Access to Capital on MSME Business Sustainability: The Moderating Role of Business Owners' Education Level - Rachel Amanda Vinka Artamefia; Jeni Susyanti; Harun Alrasyid (LP2M IAIN Palopo, 2026)
The business sustainability of MSMEs is a strategic issue in the Indonesian economy, considering their substantial contribution to Gross Domestic Product (GDP) and employment in Indonesia. However, MSME owners still face various obstacles in accessing formal financing, influenced by perceived usefulness, trust in institutions, and ease of service access. This study aims to analyze the impact of these three variables on MSME business sustainability and to examine the moderating role of the business owner's education level in this relationship. A quantitative approach with an explanatory design was employed, involving 268 MSME owners—selected via purposive sampling—who have used or are currently using financing from formal financial institutions. Data were collected using a Google Forms-based questionnaire distributed via social media and analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS) with SmartPLS software (version 4.1.1.6) to identify relationships between variables. Structural testing comprised two stages: the measurement model (outer loading, reliability, convergent validity, and discriminant validity) and the structural model (R-squared, Q² Predict, and effect size/f²), followed by hypothesis testing. The analysis results indicate that trust in financial institutions and ease of access to capital have a significant positive effect on MSME business sustainability, whereas perceived usefulness do not have a significant effect. Education level only strengthens the influence of perceived usefulness on business sustainability but does not moderate the influence of trust or ease of access to capital. These findings underscore the importance of strengthening trust in financial institutions, improving ease of access to capital, and developing the educational capacity of business owners to support MSME business sustainability.